Description and assessment of factors infl uencing on the innovation potential and the socio-economic development (for example, Mangistau region). (Journal of Economic Research & Business Administration, 2015)
This article discusses about «the innovative potential of the region» in the relation with the socio-economic development of the region: defi ned, the main factors that affect on the socio-economic development of the region, the volume of innovative products output by enterprises of the Republic of Kazakhstan regions by methods of comparison, the factors according to Gavrilov A. I. affecting on the socio-economic development of the Republic of Kazakhstan Mangistau region were analyzed (factors change the internal environment: production and resource potential, the regional market structure, human resources of the region, the regional budget, the strategy development of the region; factors of external environment analysis (direct and indirect effects): analysis of external suppliers’ goods and services, the analysis of external customers of the region, the analysis of regional competitors, the analysis of the fi nancial institutions operating in the region, transport infrastructureand technological factors and others); recommendations to improve the situation for innovative development of the companies were shown.
Keywords: Innovation potential of the region; innovation; the factors affecting on the socio-economic development of the region; socio-economic development